2005
DOI: 10.1081/bip-200048826
|View full text |Cite
|
Sign up to set email alerts
|

Two-Sided Tolerance Intervals for Balanced and Unbalanced Random Effects Models

Abstract: A procedure for constructing two-sided beta-content, gamma-confidence tolerance intervals is proposed for general random effects models, in both balanced and unbalanced data scenarios. The proposed intervals are based on the concept of effective sample size and modified large sample methods for constructing confidence bounds on functions of variance components. The performance of the proposed intervals is evaluated via simulation techniques. The results indicate that the proposed intervals generally maintain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 14 publications
0
38
1
Order By: Relevance
“…The 95% confidence interval (CI) of the probability was calculated using the delta method (Hoffman and Kringle 2005). The variance of the probability was computed from the variance of µ and the variance of X by using partial derivatives of the probability.…”
Section: Statisticsmentioning
confidence: 99%
“…The 95% confidence interval (CI) of the probability was calculated using the delta method (Hoffman and Kringle 2005). The variance of the probability was computed from the variance of µ and the variance of X by using partial derivatives of the probability.…”
Section: Statisticsmentioning
confidence: 99%
“…This idea has already been introduced in the framework of method validation 1,3,4 . These authors propose the -expectation and the -content confidence intervals as possible solutions.…”
Section: Tolerance-interval Rulesmentioning
confidence: 98%
“…The values of k E and k C depend on the experimental design used for validation and cannot be derived exactly if the design is more complicated than a simple sampling scheme. From 3,7,11,12 it can be shown that, for the general variance-component model, k E and k C can be approximated by…”
Section: Tolerance-interval Rulesmentioning
confidence: 99%
See 2 more Smart Citations